The absence of Rhodococcus equi in Mongolian horses - Takai, S. (Kitasato Univ., Towada, Aomori (Japan). School of Veterinary Medicine and Animal Sciences); Sengee, S; Madarame, H; Hatori, F; Yasuoka, K; Ochirel, E; Sasaki, Y; Kakuda, T; Tsubaki, S; Bandi, N; Sodnomdarjaa, R (Journal of Veterinary Medical Science, 2005)
In native Mongolian horses, the incidence and distribution of Rhodococcus equi are poorly understood. One hundred and four-teen equine fecal samples and 71 soil samples were collected from the camp sites of 26 nomadic families located in three areas less than 100 km from Ulaanbaatar, Mongolia. Five fecal samples were also collected from foals of Przewalski's Horses introduced into the Hustai National Park, Mongolia. No R. equi was isolated from the Mongolian horses or the soil samples. However, three colonies of R. equi were isolated from two fecal samples collected from foals of Przewalski's Horses. These isolates were avirulent, with neither 15- to 17-kDa antigens (VapA) nor a 20-kDa antigen (VapB) genes being detected. We concluded that native Mongolian horses and their environment appear free from contamination with R. equi.